Managerial Survival: Middle Manager Sense-Making during Organisational Change - Sherry Samson; Charmaine Williamson; Annemarie Davis (International School for Social and Business Studies, 2022)
Purpose: The lived experiences of middle managers within the messy realities of change offer valuable insight into how middle managers deal with disruptions. The purpose of this research was to explore the lived experiences of middle managers within the messy realities of strategising during organisational change. Study design/methodology/approach: Using a qualitative, intrinsic, single-case study grounded in Weick's sense-making theory, the sense-making practices of middle managers during organisational change were explored. Data was gathered through email journals over four months and enabled real-time tracking of microlevel strategising after change implementation. A constructionist form of thematic analysis was adopted and explored middle managers' organisational social reality. Findings: Sense-making occurs on a cognitive and emotional level. Participants attached meaning to actions and thereby created a sense for themselves and others towards organisational security and sustainability. Middle managers reframed the constraining organisational context through embodied sense-making for practical coping, which enabled them to rise above the organisational complexity and contradiction. Originality/value: Recommendations are offered to support middle managers during organisational change.